Kali Linux network scanning cookbook : over 90 hands-on recipes explaining how to leverage custom scripts and integrated tools in Kali Linux to effectively master network scanning /: over 90 hands-on recipes explaining how to leverage custom scripts and integrated tools in Kali Linux to effectively master network scanning. (2014) - Unknown
No abstract available